Transarterial chemoembolization combined with apatinib in the treatment of advanced hepatocellular carcinoma: a prospective, multi-center, real-world study (Ahend-HAP02) - Hang Yuan; Zhen Li; Guang-Shao Cao; Fei Xu; Gang Wu; Peng-Xu Ding; Qiu-Liang Wei; Zu-Kuan Chang; Cheng Xing; Huan-Zhang Niu; Jun Yin; Quan-Jun Yao; et al. (Frontiers in Oncology, 2025)
PurposeTo analyze the efficacy and safety of transarterial chemoembolization (TACE) with apatinib (TACE-A) for the treatment of advanced hepatocellular carcinoma (HCC).MethodsData from advanced HCC patients treated with TACE-A between January 2019 and June 2022 were evaluated. The patients from 8 medical centers were included. The primary endpoints were overall survival (OS) and progression-free survival (PFS). The secondary endpoints were objective response rate (ORR) and adverse events (AEs). Prognostic factors affecting OS were analyzed, and the tumor imaging response at the first follow-up was evaluated to study the survival differences among patients.ResultsA total of 389 patients were included, the median PFS was 7.0 months (95% confidence interval [CI]: 6.3–7.7), and the median OS (mOS) was 18.9 months (95% CI: 17.5–20.3). The median time of the first follow-up was 1.2 months, the ORR was 33.7%, and the mOS of the complete response, partial response, stable disease, and progressive disease groups were 30.1, 20.9, 18.5, and 12.9 months, respectively. The difference was statistically significant (p < 0.05). Univariate and multivariate Cox regression analyses demonstrated that the prognostic factors affecting OS were distant metastasis, maximum tumor diameter, TACE duration, and alpha-fetoprotein (AFP) level (p < 0.05). The overall incidence of grade 3 and above AEs was 18.0% (70/389), and the overall safety was controllable.ConclusionTACE-A significantly improved OS, PFS, and ORR in advanced HCC patients. At the first follow-up patients with a poor tumor response had a poor prognosis. Distant metastasis, maximum tumor diameter, TACE frequency, and AFP levels are important prognostic factors that affect OS in patients. AEs of combination therapy are safe and manageable.Clinical trial numberChinese Clinical Trials Database (ChiCTR1900024030).